Identifikasi Risiko dan Pemecahan Masalah Bagian Finance di PT Erajaya - Givira, Shania; Rudyanto, Astrid (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2024)
PT Erajaya Swasembada Tbk., known as Erajaya, is a leading company in Indonesia in the field of distribution and retail of electronics, lifestyle, health, and food products. The community service program conducted by STIE Trisakti aimed to improve the accuracy of the company's financial data, which faced issues of inaccuracy. Through the methods of risk analysis, fishbone diagram, SMART, and PDCA, STIE Trisakti successfully identified the root causes and proposed relevant solutions. The conducted socialization and training activities effectively reduced data input errors and enhanced the quality of PT Erajaya Swasembada Tbk.'s financial reports, thus highlighting the importance of risk management and continuous improvement in maintaining the reliability of the company's financial data.